THE SPECIFIC HEATS OF LaNi5, GdNi5 AND TbNi5 COMPOUNDS BETWEEN 2 AND 50 K (Sciences & Technology. A, exactes sciences, 2003)
The specific heats of the intermetallic rare earth compounds LaNi5, GdNi5 and TbNi5 have been investigated in the temperature range 2 to 50K in order to reexamine the low temperature specific heat of the non-magnetic LaNi5 compound and to study the magnetic contributions to the specific heat in the magnetic GdNi5 and TbNi5 compounds around their Curie temperatures. The low temperature specific heat of the LaNi5 compound shows an unusual anomaly.The magnetic specific heats of the GdNi5 and TbNi5 compounds show l-type anomalies. These compounds show other anomalies at about 3.8 K and 2.4 K respectively. These anomalies have been  attributed to the presence of Gd2O3 and Tb2O3 magnetic compounds as impurities.